PENENTUAN DOSIS FORMULASI PUPUK ORGANIK UNTUK EFISIENSI PENGGUNAAN PHONSKA PADA TANAMAN JAGUNG MANIS (Zea mays sacharata Sturt.) - Tulungen, A. G.; Tumewu, P.; Montolalu, M.; Rantung, John L.; Tulung, S. (EUGENIA, 2019)
The use of organic fertilizer provides soil with macronutrients, micronutrients, and organic acids which improve the long-term physical, chemical, and biological fertility of the soil. This research aims to: 1) Increase physical and chemical soil fertility, 2) Acquire the interaction between organic fertilizer and Ponska fertilizer dosage on sweet corn crops, 3) Acquire the most efficient dosage of PONSKA  fertilizer on sweet corn, and 4) disseminate research results through journal articles and directly to farmers.  This research will increase the efficiency of NPK Ponska chemical fertilizers by utilizing waste from around the farm and lakes to formulate organic fertilizer to apply on sweet corn crops and as a reference to teaching material. Factorial research with two factors was designed using a randomized block design. Factor I (A) = Organic fertilizer formulation, comprising of A1 = 20 ton/ha, A2 = 30 ton/ha, and A3 = 40 ton/ha.  Factor II (B) =  Phonska fertilizer,  comprising of B1 = 25 % Ponska, and B2 = 50% Ponska. Every treatment was replicated four times, yielding 24 research plots. Response variables observed were: Plant height, number of leaves, dry weight of the plant. Data were analyzed using ANOVA, followed by Tukey's honest significance difference test (alpha = 0.05) if significant differences were found. Results showed that the interaction between organic and Phonska fertilizer formulations had significant effects on plant height. A dosage of 40 ton/ha of organic fertilizer can decrease the use of phonska fertilizer by 75% based on the height of sweet corn plants.